THE IGNATIAN SPIRITUAL EXERCISES AS A PRACTICE OF INTER-RELIGIOUS EDUCATION - Setyawan, Andreas (Sanata Dharma University, 2025)
The Spiritual Exercises (SpEx), written by Ignatius of Loyola (1491-1556), offer significant perspectives on religious education theory and practice. This research addresses how such a spirituality can be practiced as interreligious education without overlooking its confessional nature. Employing library research, it offers a content analysis of SpEx through the framework of communicative theology developed by Matthias Scharer and Bernd Jochen Hilberath, which facilitates interreligious education by presupposing fundamental panentheistic ideas, employing synchronic and diachronic approaches through its three-level theology and four-factor religious identity, and incorporating nonverbal communication actions. SpEx fulfils these religious principles by embracing the conviction that God is to be discovered in all things, employing a cura personalis approach, and engaging in personal prayer. SpEx can serve as a model for interreligious education by drawing on the Ignatian educational framework, which includes the phases of context, experience, reflection, action, and evaluation. This paradigm can be incorporated into a fractal model illustrating the dynamics of religious identity, constructed from four factors (I, We, It, and Globe) that manifest at the levels of concrete experience, experiential reflection, and scientific reflection, transcending the collective memory of a specific religious tradition.